Evaluación del clima organizacional y su incidencia en el desempeño laboral del personal de la clínica San Francisco de Cayambe, provincia de Pichincha - Recalde Arciniega, Joysbel Stefania (2023)
The report of the Final Degree Project 'Evaluation of the organizational climate and its impact on the work performance of the staff of the San Francisco de Cayambe Clinic, province of Pichincha', a work that proposes the implementation of strategies for the improvement of the organizational climate, a variable that According to the results of the study, it presents indicators that do not reach optimal levels of incidence in work performance. In the study, an interview was applied to the management of the Clinic\; In addition, it was based on the measurement of the organizational climate through the application of a questionnaire on the Likert scale applied to the personnel (20)\; Three dimensions were measured: Interpersonal relationships, Self-actualization and Stability - change\; For the measurement of work performance, three dimensions were evaluated: Labor productivity, Characteristics of work capacity and Communication - empathy. For the data analysis, the Spearman association coefficient test was applied, an analysis that allowed us to identify the work environment factors that negatively influence work performance\; The dimensions that reflect low levels in the quality of the work environment are: involvement, cohesion, boss motivation, and interest and initiative to complete the job, dimensions that influence identification with the work environment, lack of knowledge of the institutional philosophy and active participation in work meetings. From the analysis it is determined that the implementation of strategies will allow to determine the areas that weaken the work environment and that in turn will be oriented to the improvement of work performance.